Meta-Review on the Effectiveness of Classroom-Based Psychological Interventions Aimed at Improving Student Mental Health and Well-Being, and Preventing Mental Illness - Šouláková, Barbora; Kasal, Alexandr; Butzer, Bethany; Winkler, Petr (The journal of primary prevention, 2019)
This meta-review summarizes existing evidence from systematic reviews and meta-analyses on the effectiveness of school-based psychological interventions aimed at improving student mental health and well-being, and preventing mental illness. Systematic reviews and meta-analyses were identified via the electronic databases PsycINFO, Web of Knowledge, Medline, Embase, and HMIC (Health Management Information Consortium). Ten systematic reviews and meta-analysis were eligible for inclusion in the final analyses. These systematic reviews and meta-analyses evaluated the effects of five types of school-based psychological interventions: Mindfulness, Social Emotional Learning, Cognitive Behavioral Therapy, Yoga, and Body-Image. Overall effectiveness reported in the included studies was significant for the most part, and ranging from small to large with respect to the effect size. The authors of all of the studies emphasized the need for additional high-quality trials to further examine the effectiveness of school-based psychological interventions aimed at improving student mental health and well-being, and preventing mental illness.
Keywords: Students; School Health Services; Mental health; Humans; Mental Health; School intervention; lidé; Emotional Adjustment; duševní zdraví; emoční nastavení; mladiství; studenti; Child; dítě; Adolescent; Prevention; školní zdravotnické služby; Psychological intervention; duševní poruchy; Mental Disorders; Review